(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The problem of maintenance of acceptable food strength security is considered in the article. Food safety certainly as an important constituent of national safety in conception of development agrarian of industrial complex. It is well-proven that the poultry farming is one of the most dynamic industries of stock-raising of Ukraine that is able to improve food safety of Ukraine. Poultry is one of those sectors of agriculture, whose development enables improved rapidly meet the growing demand for high quality food products of animal origin, that directly affects food security. In the article the modern trends in the field of poultry in Ukraine in the context of the statistical analysis of the dynamics of livestock, production of basic products – poultry and eggs, economic efficiency implementation. It is set that substantial increase of production of meat of bird volumes maybe only on condition of favourable investment climate in industry, that is stipulated by the stable, forecast public policy in support a home commodity producer in budgetary, credit, price spheres of state administration, and also in adjusting of producing of technological equipment taking into account innovative technologies. Terms, threats and factors of providing of food safety of Ukraine, are certain by the national production of goods of industry of the poultry farming.